Ultimate compressive capacity of tapered concrete-filled double skin steel tubular stub columns with large hollow ratio. (September 2022) - Zhang, Dongliang; Li, Wei; Fu, Kun; Li, Tianhao; Deng, Ran; Wang, Yuhang
Abstract: Recent developments in towers of wind turbine have heightened the need for tapered Concrete-Filled Double Skin Steel Tubular columns with Large Hollow Ratio (LHR-CFDST). It is necessary to further investigate the mechanical behaviour, key parameters' effects and design methods of tapered LHR-CFDST columns. This paper thus presents an analytical study on the tapered LHR-CFDST stub column under axial compression. A comprehensive finite element (FE) modelling is developed and then verified with the experimental data. A parametric study is conducted to reveal the effects of tapered angles, hollow ratios and diameter to thickness ratios of steel tubes. Further analysis is carried out to understand the compressive behaviour in terms of the full-range load-deformation relation, the axial compressive force distribution and the limitation of steel tube's diameter to thickness ratio. A simplified method for predicting the ultimate compressive capacity of tapered LHR-CFDST stub columns is proposed and the prediction agrees well with the test data. Highlights: Comprehensive finite element models are developed and verified by experimental data. Parametric studies on the behaviour of tapered LHR-CFDST columns are conducted. Numerical analyses are conducted and mechanism of the column is discussed. A simplified method for predicting the ultimate compressive capacity is proposed.